Aplikasi Paclobutrazol untuk Optimalisasi Pertumbuhan Jahe Merah (Zingiber officinale var. Rubrum): Paclobutrazol Application for Red Ginger (Zingiber officinale var. Rubrum) Growth Optimization - Gut Tianigut; Onny Chrisna Pandu Pradana; Miranda Ferwita Sari (J-Plantasimbiosa, 2022)
Red ginger is one of the herb plants that is widely used throughout the world, it can be used as spices, seasonings, raw materials for the traditional medicine industry, Phyto-pharmacy, healthy food and drinks, and also cosmetic and body care products. From 2014—2018 ginger production in Indonesia fluctuated with a growth rate of -36.36% 2018. The application of growth regulators in ginger cultivation can be an alternative to encouraging increased productivity and improving ginger quality. This research aimed to investigate the growth response of red ginger in various concentrations of growth regulator (paclobutrazol) and to obtain the optimum concentration of growth regulator (paclobutrazol) on stimulating red ginger growth. This research was conducted in Politeknik Negeri Lampung, from June to October 2020. Treatments were single-arranged in a completely randomized block design with three replications, each replication consisted of two samples, and each sample consisted of two subsamples. The treatments tested were five levels of paclobutrazol as a growth regulator (0 ml.l-1, 2 ml.l-1, 4 ml.l-1, 6 ml.l-1, and 8 ml.l-1). The result of this research showed that the best growth response of red ginger was obtained on the application of 4 ml.l-1 paclobutrazol. Keywords: red ginger, paclobutrazol, polynomial orthogonal